2012
DOI: 10.1039/c2dt11651k
|View full text |Cite
|
Sign up to set email alerts
|

2-Line ferrihydrite: synthesis, characterization and its adsorption behaviour for removal of Pb(ii), Cd(ii), Cu(ii) and Zn(ii) from aqueous solutions

Abstract: Nano-structured 2-line ferrihydrite was synthesized by a pH-controlled precipitation technique at 90 °C. Chemical, X-ray diffraction (XRD), Fourier transform infrared (FTIR) and Raman analyses confirmed the sample to be 2-line ferrihydrite. The nano nature of the prepared sample was studied by transmission electron microscopy (TEM). The surface area obtained by the Brunauer-Emmett-Teller (BET) method was 175.8 m(2) g(-1). The nanopowder so obtained was used to study its behaviour for the removal of Pb(II), Cd(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 51 publications
6
69
1
1
Order By: Relevance
“…Our results indicating the high retention of phosphate, arsenate and lead by ferrihydrite are in good agreement with published data [26,27,28]. Poorly crystalline ferrihydrite, which has a high surface area, shows high retention capacity, but also so too do soils with high ferrihydrite content [29].…”
Section: Discussionsupporting
confidence: 81%
“…Our results indicating the high retention of phosphate, arsenate and lead by ferrihydrite are in good agreement with published data [26,27,28]. Poorly crystalline ferrihydrite, which has a high surface area, shows high retention capacity, but also so too do soils with high ferrihydrite content [29].…”
Section: Discussionsupporting
confidence: 81%
“…Cd 2 þ concentration is decreased to 0.0015 mg L À 1 , which is far lower than the drinking water quality standards (0.005 mg L À 1 ) set by WHO [32]. However, most reports basically have been focused on the removal of high concentration Cd 2 þ from water and the final Cd 2 þ concentration is still higher than 0.06 mg L À 1 after treatment [33][34][35][36]. Furthermore, we also study the adsorption dynamics of the mesoporous TiN microspheres, as shown in Fig.…”
Section: þ Removal Testmentioning
confidence: 82%
“…(2014) [1][2][3][4][5][6][7][8][9][10][11][12][13] www.deswater.com doi: 10.1080/19443994.2014.972986 phosphate fertilizers, and electroplating and manufacturing of batteries, pigments, and screens [5,7,8].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Heavy metal pollution of wastewater is always considered as the most common environmental threat due to the fact that venomous metal ions are potentially able to reach the top of the food chain and thus become a risk agent for human health [1][2][3][4]. In this regard, cadmium(II) is a toxic ion with significant environmental and occupational concerns [5,6].…”
Section: Introductionmentioning
confidence: 99%